Enhancing Public Service Delivery Through Emergency Social Programs: A Case Study of Jabar Quick Response Implementation in West Java Province - Ihsan Wanfora; Ai Siti Farida (Khazanah Multidisiplin, 2025)
The increasing complexity of social problems in the digital era demands governments to respond innovatively and swiftly. Jabar Quick Response (JQR), launched by the Governor of West Java, exemplifies an emergency program intended to expedite responses to urgent social and humanitarian issues. This study investigates the implementation of JQR through Edward III’s framework, focusing on communication, resources, disposition, and bureaucratic structure. Employing a qualitative descriptive method with primary data from interviews and observations, and secondary data from official documents, this research analyzes how JQR addresses public complaints and social emergencies. Findings reveal that although the program has achieved significant progress in providing a swift response mechanism, challenges persist, including limited funding, insufficient public awareness, and fragmented coordination among stakeholders. This paper contributes to the discourse on public administration by highlighting the necessity of adaptive governance, collaborative networks, and strategic communication in emergency response programs.